1-D model for finding geometry of a single phase ejector. (15th December 2018) - Kumar, Vikas; Sachdeva, Gulshan
Abstract: This paper presents a novel 1-D mathematical model to determine complete dimensions of an ejector component of Ejector Refrigeration System (ERS). The concepts of Prandtl's mixing length, Prandtl-Meyer expansion wave, Kelvin-Helmholtz instability and Baroclinic effect are introduced in the model to precisely determine the various diameters, mixing length, nozzle exit position etc. for the given conditions of the primary & secondary fluid, cooling capacity and critical condenser pressure. The area ratios obtained using the mathematical model are compared with the experimental/numerical results available in open literature for the same operating conditions and are found to be in good agreement. Moreover, ejector geometry determined from the proposed model is analyzed using CFD for the same input conditions. Average deviation in the entrainment ratio obtained using CFD and that given to the model is found to be less than 2.48% and thus model is validated again. The experimental test rig of ejector refrigeration system is also fabricated and the performance is evaluated while operating at critical condenser pressure. The deviation in the ejector geometry used in the experiment is found to be less than 7% in comparison to the ejector dimensions calculated by the numerical model for the same input conditions. Highlights: 1-D model is proposed to calculate complete geometry of ejector. Novel concepts are introduced to accurately predict the dimensions of ejector. Primary and secondary nozzle is influenced by generator and condenser respectively. Performance and operating range of ejector depend on the geometry of ejector. Effect of ejector inputs are found on its geometry.